The National Jawi Script and Technology Seminar 2012 - Saharudin, Ramli; Zuraina, Ali (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
18 October 2012. The National Jawi Script and Technology Seminar 2012 was successfully organised by CMLHS. The seminar involved 500 participants, which included UMP associates and students, school students as well as staff from government and private organisations in Pahang. The objective of the seminar was to expose participants to the understanding and awareness of technology in empowering the Jawi script to the society.